Everyday Choice Making: Outcomes of Young People with Acquired Brain Injury After Moving from Residential Aged Care to Community-Based Supported Accommodation. Issue 3 (26th January 2016) - Winkler, Dianne; Callaway, Libby; Sloan, Sue; Holgate, Nadine
Abstract : Objectives: (1) Examine the opportunities young people with acquired brain injury (ABI) have to make everyday choices after moving out of residential aged care (RAC) into community-based shared supported accommodation (SSA); (2) Compare everyday choice making of this group with a group of people with ABI living in RAC. Research design: Mixed methods comparing two independent groups. Method and procedures: Responses on eleven relevant items of the Resident Choice Scale (RCS) were compared between two groups; 45 people with ABI living in RAC and 20 people with ABI who had moved from RAC to live in SSA. In addition, the choice making experiences of the SSA group were investigated through semi-structured interviews with the individual and/or their family member. Interviews were recorded, transcribed and thematically analysed. Results: Greater opportunities for everyday choice making were demonstrated on 10 out of the 11 RCS items for people living in SSA, compared to RAC. These included improved choice regarding meals, bedtime and leisure activities. Qualitative data also illustrated new choice opportunities afforded to the SSA group. Five key themes relating to choice were identified: rules and routines, communication, things to do, food and home-like environment . Conclusions: Community-based, age-appropriate and small-scale supported accommodation provides people with ABI more opportunities for everyday choice making than RAC.